ナンキョクカイ インドヨウ ク ニ オケル ナンキョクオキアミ ノ セツエ - 澤本, 彰三; サワモト, ショウゾウ; 菊野, 秩; キクノ, ツカサ; 菅井, 準一; スガイ, ジュンイチ; 小牧, 勇蔵; コマキ, ユウゾウ; Sawamoto, Shozo; Kikuno, Tsukasa; Sugai, JunIchi; Komaki, Yuzo (1983)
P(論文) BIOMASS研究FIBEX航海が1980/1981に水産庁開洋丸によりインド洋海区において実施された。この機会を利用してナンキョクオキアミ(Euphausia superba)の摂餌行動の観察を行った。調査は, 1980年12月中・下旬の第1期, 1981年1月中・下旬の第2期, 2月上旬の第3期にわたって実施された。材料は, 表面びきORIネットと魚群探知機とネットレコーダーを利用したKOC-A中層びきネットによって採集したナンキョクオキアミを用いた。胃および体節により区分した消化管に内容物のある個体の出現状況を成熟個体の雌雄, 未成熟個体, 幼令個体ごとに経時的に追跡した。また, 同一の群れを経時的に追跡採集を行い, 垂直移動にともなう摂餌行動の変化をおった。以上の調査の結果, 第1期, 第2期ともに, 摂餌は1日2回, 正午過ぎ(12時～15時)と早朝早く(0時～3時)にピークが見られた。雄, 雌について特に明瞭な差はみられないが, 幼令個体では摂餌が不活発で, 摂餌時間帯も不明瞭であった。第3期は, どのグループも明瞭な摂餌時間帯がなく, また摂餌も不活発であった。同一群からの繰り返し採集調査では, 明瞭な結果は得られなかったが, 幼令個体の摂餌はやはり不活発であった。 The BIOMASS FIBEX Cruise of R/V KAIYO MARU in the Indian Sector of the Antarctic Ocean was conducted from 11 November, 1980 to 18 March, 1981. The investigation could be subdivided into three stages on the basis of the area and the duration : Investigation I (11-26 December, 1980; Long. 60-85°E), Investigation II (16-30 January, 1981; Long. 30-55°E) and Investigation III (31 January-6 February, 1981; Long. 60-70°E). Feeding activity of the Antarctic krill, Euphausia superba DANA, was studied regarding the sexual maturation by examining the digestive tract contents. It seemed that feeding of the krill was active two times a day. In Investigation I the active period of feeding was between 00 and 03h and 12 and 15h or between 12 and 18h in both sexes. With the advance of time (Investigation III) the active period of feeding was different between sexes, and the feeding activity varied little in mature female. From the present examination it was difficult to confirm the relation between the population density causing vertical migration and the feeding activity. departmental bulletin paper